Life-long learning materials enabling the growth of Digital Twin competences - Ashok Kumar, Alalvanan; Jagadeeswar, Rahul Rao (My University, 2023)
In recent times, Digital Twin and Discrete Event Simulations are some of the promis- ing technologies in enabling industry 4.0. Since the developments of these technolo- gies are recent, their definitions and representations vary. Accordingly, there is a need to develop learning materials for these concepts to better help users seeking to develop or improve in these areas academically and professionally. The thesis fo- cuses on the main goal, which is the creation of learning materials with an emphasis on lifelong learning. For this, the learning materials are developed on the guidelines of constructive alignment and Bloom’s taxonomy to better facilitate lifelong learn- ing among the users. The developed learning materials are also developed around real-world problems such that the content is relatable and relevant. In the next phase, the evaluation of these learning materials is done. This is done by procuring feedback from the focus groups stakeholders, industry-level simulation experts, self-analysis and reflection; the pilot study undergoes revision and necessary changes are made. The procured revised learning material hopes to serve as a guide for users seeking to develop learning materials to improve competence in the field of Digital Twin and Discrete Event Simulation.
Keywords: Bloom’s Taxonomy, Constructive alignment, Digital Twin, Discrete event simulation, Lifelong learning material.